Protection From The Government Related To Manpower Rights Handling Covid-19 Patients - Hendro Suwono (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Health workers have a very important role in the implementation of health efforts carried out in terms of providing health services for the community in accordance with laws and regulations. During the Covid 19 pandemic it was recorded that a number of medical personnel died due to exposure to Covid 19. This legal research aims to determine the role of the government in providing protection for medical personnel who handle Covid 19.